2014
DOI: 10.2215/cjn.02540313
|View full text |Cite
|
Sign up to set email alerts
|

Tubulointerstitial Nephritis with Uveitis in Chinese Adults

Abstract: SummaryBackground and objectives Tubulointerstitial nephritis and uveitis (TINU) syndrome is considered a rare cause of acute tubulointerstitial nephritis (ATIN) that is usually associated with renal recovery. This study sought to investigate the diagnosis, prognosis, and contributing factors of TINU syndrome using a large cohort of patients with prospective follow-up.Design, setting, participants, & measurements This study included patients with TINU syndrome from a prospective cohort of patients with ATIN fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 34 publications
(36 reference statements)
6
98
2
3
Order By: Relevance
“…The diagnosis of TIN or TINU is difficult because of variable and nonspecific clinical manifestations. Studies have reported that urinary α1-microglobulin and β2-microglobulin excretion increase in patients with TINU (20,21). The current results indicated that urinary α1-microglobin increased significantly (about 100-fold above the upper limit of the normal range) in the 6 patients with ATIN and in the 4 patients with TINU, and the ratio of urinary α1-microglobulin to microalbumin was greater than 1.…”
Section: Resultssupporting
confidence: 54%
“…The diagnosis of TIN or TINU is difficult because of variable and nonspecific clinical manifestations. Studies have reported that urinary α1-microglobulin and β2-microglobulin excretion increase in patients with TINU (20,21). The current results indicated that urinary α1-microglobin increased significantly (about 100-fold above the upper limit of the normal range) in the 6 patients with ATIN and in the 4 patients with TINU, and the ratio of urinary α1-microglobulin to microalbumin was greater than 1.…”
Section: Resultssupporting
confidence: 54%
“…14,19,20 Yin Tang et al 14 and Li et al 21 demonstrated for the first time a high prevalence of serum autoantibodies against modified C-reactive protein (anti-mCRP autoantibodies) in patients with TINU syndrome. 14 The results of Ying Tang suggest that mCRP may be one of the common target autoantigens in renal and ocular tissues in patients with TINU syndrome.…”
mentioning
confidence: 99%
“…Specific basement membrane antigens have also been found to be immunogenic in animal models of acute interstitial nephritis, and only few patients with TINU were specifically reported to have immunofluorescent tubular basement membranes (TBMs) staining indicating antibody deposition [8,11,23]. It has been also reported a tubular depositions of complement components such as C3 and the C5b-9 complex [6]. On the other hand, TINU syndrome has sometimes been associated with polyclonal hypergammaglobulinemia and elevated serum immunoglobulin IgG levels suggesting a humoral mediated immune response [24], as in our tow patients.…”
Section: Discussionmentioning
confidence: 99%
“…TINU syndrome is a disorder characterized by a combination of idiopathic acute tubulointerstitial nephritis and uveitis [4,5], Since it was first documented in 1975 [6,7], only a little more than 200 cases of TINU syndrome have been reported [8,9], with approximately 60% of cases occurring in children [6]. Most of the patients with TINU syndrome are adolescents and young women, with a median age at the onset of 15 (range 9 to 74) years and a 3:1 female-to-male predominance [2,7], but others found an older age group with a male predominance [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation